ENHANCING OPERATIONAL AGILITY THROUGH DIGITAL PROCESS INTEGRATION AND SUPPLY CHAIN VISIBILITY: THE MEDIATING ROLE OF DECISION-MAKING SPEED IN SERVICE FIRMS - Heriswanto Heriswanto; Firman Firman; Suriyanti; Ramlawati (Accounting Profession Journal (APAJI), 2026)
This study examines the role of digital process integration and supply chain visibility in enhancing operational agility, with decision-making speed as a mediating variable in service firms. Using a quantitative approach, data were collected from 195 respondents across major cities in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital process integration has a positive and significant effect on both decision-making speed and operational agility, although its direct impact on agility is relatively modest. In contrast, supply chain visibility does not significantly influence operational agility directly, but exerts a strong indirect effect through decision-making speed, indicating a full mediation. Furthermore, decision-making speed is identified as a key determinant of operational agility, highlighting its critical role in translating digital capabilities into responsive actions. These results suggest that digital investments alone are insufficient to achieve agility unless supported by rapid and effective decision-making processes. The study contributes to the literature by proposing a decision-centric perspective of digital transformation, emphasizing the importance of organizational responsiveness over mere technological adoption. Practically, the findings encourage managers to align digital systems with decision processes to maximize agility outcomes.